2014
DOI: 10.4238/2014.january.21.20
|View full text |Cite
|
Sign up to set email alerts
|

Association of a CYP4A11 polymorphism and hypertension in the Mongolian and Han populations of China

Abstract: ABSTRACT. Human cytochrome P450 4A11 (CYP4A11) plays a role in the regulation of blood pressure through the conversion of arachidonic acid into 20-hydroxyeicosatetraenoic acid (20-HETE). We therefore investigated the association between a CYP4A11 polymorphism (rs9333025) with hypertension in the Mongolian and Han ethnic groups. We studied 514 Mongolians in a pastoral area, including 201 hypertension patients and 313 normotensive controls, and 524 Han individuals in an urban area, including 215 hypertension pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…We showed that the CYP4A11 rs9333025 variation, but not CYP4A11 rs2269231, CYP4F2 rs2108622, or CYP4F2 rs3093135, was independently associated with IS. These results are consistent with those of previous studies (Fu et al, 2008a(Fu et al, , 2008c(Fu et al, , 2012Liang et al, 2014) and suggest that mutations in CYP4A11 may contribute to altered 20-HETE production, which could ultimately lead to increased risk for stroke.…”
Section: Discussionsupporting
confidence: 92%
“…We showed that the CYP4A11 rs9333025 variation, but not CYP4A11 rs2269231, CYP4F2 rs2108622, or CYP4F2 rs3093135, was independently associated with IS. These results are consistent with those of previous studies (Fu et al, 2008a(Fu et al, , 2008c(Fu et al, , 2012Liang et al, 2014) and suggest that mutations in CYP4A11 may contribute to altered 20-HETE production, which could ultimately lead to increased risk for stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were consistent with those of previous studies (Fu et al, 2008a;Ding et al, 2010;Liang et al, 2014), but contradicted the findings of some other studies (Fava et al, 2008;Fu et al, 2008b;Ward et al, 2008;Deng et al, 2010;Munshi et al, 2012). For instance, Ward et al (2008) reported that a single polymorphism in the CYP4F2 gene, but not the CYP4A11 gene, is associated with increased 20-HETE secretion and BP.…”
Section: Discussioncontrasting
confidence: 46%
“…Also, in humans a deficiency in 20-HETE synthesis and/or action, measured as decreased urinary excretion in response to salt loading, has been linked to salt-sensitive hypertension (Laffer et al, 2008; Laffer, Laniado-Schwartzman, Wang, Nasjletti, & Elijovich, 2003a; Laffer, Laniado-Schwartzman, Wang, Nasjletti, & Elijovich, 2003b). Polymorphisms in the CYP4A11 gene that reduce its catalytic activity by more than 50% are associated with a decrease in the urinary excretion of 20-HETE and the development of salt-sensitive hypertension (Gainer et al, 2005; Gainer et al, 2008; Laffer et al, 2008; Liang et al, 2014; Mayer et al, 2006). …”
Section: -Hete and Vascular Functionmentioning
confidence: 99%